Capabilities, Opportunities, Resources and Environments (CORE): Using the CORE approach for inclusive, occupation‐centred practice. (19th January 2020) - Pereira, Robert B.; Whiteford, Gail; Hyett, Nerida; Weekes, Gemma; Di Tommaso, Amelia; Naismith, James
Abstract: Background/Aim: Occupational participation is often claimed as a human right and determinant of health by occupational science and therapy scholars. Yet, maintaining occupation at the centre of practice is a challenge. The Capabilities, Opportunities, Resources and Environments (CORE) approach provides a mechanism for occupational therapists to address this challenge by viewing their practice through an inclusive lens, and enacting inclusive, occupation‐centred occupational therapy. This paper presents applications of the CORE approach via three case narratives. The aim is to increase occupational therapists' understanding of how to apply the CORE approach and to facilitate research‐to‐practice knowledge translation. Methods: The CORE approach is introduced and applied through three case narratives, each highlighting one of the CORE elements within the context of the broader approach. Findings: The narratives contain critical reflective case narratives on the application of the CORE approach in the context of three different practice settings in Australia based on the authors' experiences. Practice settings include working within the National Disability Insurance Scheme, in a secure forensic mental health facility, and in rural community health. The forensic health case narrative documents findings from the authors' research which applied the CORE approach as an analytical tool, providing an additional layer of analysis of the identified themes from the original study. Conclusion: This paper provides occupational therapists with a practical understanding of how to apply the CORE approach through diverse case narrative examples. The practical "how to" questions that guided the development of the case narratives can be used by occupational therapists and occupational therapy students in individual or group critical reflection to support development and application of socially inclusive and occupation‐centred praxis. If occupational therapists are to claim expertise in enabling occupation and social inclusion, then using the CORE approach is vital to designing and implementing inclusive, occupation‐centred interventions.